Contralateral Hemispheric Cerebral Blood Flow Measured With Arterial Spin Labeling Can Predict Outcome in Acute Stroke. Issue 12 (December 2019) - Thamm, Thoralf; Guo, Jia; Rosenberg, Jarrett; Liang, Tie; Marks, Michael P.; Christensen, Soren; Do, Huy M.; Kemp, Stephanie M.; Adair, Emma; Eyngorn, Irina; Mlynash, Michael; Jovin, Tudor G.; et al.
Abstract : Background and Purpose—: Imaging is frequently used to select acute stroke patients for intra-arterial therapy. Quantitative cerebral blood flow can be measured noninvasively with arterial spin labeling magnetic resonance imaging. Cerebral blood flow levels in the contralateral (unaffected) hemisphere may affect capacity for collateral flow and patient outcome. The goal of this study was to determine whether higher contralateral cerebral blood flow (cCBF) in acute stroke identifies patients with better 90-day functional outcome. Methods—: Patients were part of the prospective, multicenter iCAS study (Imaging Collaterals in Acute Stroke) between 2013 and 2017. Consecutive patients were enrolled after being diagnosed with anterior circulation acute ischemic stroke. Inclusion criteria were ischemic anterior circulation stroke, baseline National Institutes of Health Stroke Scale score ≥1, prestroke modified Rankin Scale score ⩽2, onset-to-imaging time <24 hours, with imaging including diffusion-weighted imaging and arterial spin labeling. Patients were dichotomized into high and low cCBF groups based on median cCBF. Outcomes were assessed by day-1 and day-5 National Institutes of Health Stroke Scale; and day-30 and day-90 modified Rankin Scale. Multivariable logistic regression was used to test whether cCBF predicted good neurological outcome (modified Rankin Scale score, 0–2) at 90 days. Results—: Seventy-seven patients (41 women) met the inclusion criteria with median (interquartile range) age of 66 (55–76) yrs, onset-to-imaging time of 4.8 (3.6–7.7) hours, and baseline National Institutes of Health Stroke Scale score of 13 (9–20). Median cCBF was 38.9 (31.2–44.5) mL per 100 g/min. Higher cCBF predicted good outcome at day 90 (odds ratio, 4.6 [95% CI, 1.4–14.7]; P =0.01), after controlling for baseline National Institutes of Health Stroke Scale, diffusion-weighted imaging lesion volume, and intra-arterial therapy. Conclusions—: Higher quantitative cCBF at baseline is a significant predictor of good neurological outcome at day 90. cCBF levels may inform decisions regarding stroke triage, treatment of acute stroke, and general outcome prognosis. Clinical Trial Registration—: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02225730. Abstract : Supplemental Digital Content is available in the text.